SPEAKING OF ADOLESCENT FEMALE GENDER OF A PUBLIC SCHOOL ABOUT THE FORTRESS OF AESTHETIC STANDARDS CULTURALLY TAXES TO BODY (Fiep Bulletin - online, 2015)
Adolescence is a stage of life characterized by the transition, conflicts and body dissatisfaction which enhances psychological disorders, concerns about weight and appearance.The pressure to have the perfect body exerted by the media, family and peers, undertakes the training of young people who are taken to internalize ideal unattainable beauty. These aspects are compounded taking into account that another striking feature in adolescence is the difficulty in expressing their emotions. Given this situation, the present article intends to contribute to the discussions, demonstrating an understanding of the adolescent participants of a study using focus group in a public school in Fortaleza on the imposition of lean and athletic aesthetic standard. The research universe was formed by teenagers of high school in the morning and afternoon shifts. The option for females was due to the fact that the woman's body to be more susceptible to aesthetic standards imposed by society. We take anthropometric measurements and calculate BMI. The students were divided into groups according to BMI, using the percentiles 15 and 85 for each age group. Adolescents with BMI values below the 15th percentile were organized in the group of "stunted" adolescents with BMI between the 15th and 85th percentiles were considered "well-nourished", while adolescents with a BMI above the 85th percentile were classified as "group on weight ". We conclude that physical activity, especially weight training, was the most frequent means to achieve the ideal body and adolescents on weight sought become more lean and underweight worship an athletic body to approach the beauty standard culturally acceptable.
Keywords: Body image. Teens. Focal group. Aesthetic standard.